2007
DOI: 10.1074/jbc.m610769200
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasopressin-mediated Cardiac Differentiation

Abstract: Despite the existence of a functional arginine vasopressin (AVP) system in the adult heart and evidence that AVP induces myogenesis, its significance in cardiomyogenesis is currently unknown. In the present study, we hypothesized a role for AVP in cardiac differentiation of D3 and lineage-specific embryonic stem ( The neurohypophyseal hormone arginine vasopressin (AVP) 2 is essential for cardiovascular homeostasis. AVP is involved in the regulation of body fluid osmolality, blood volume and pressure via the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…V1AR-mediated protein synthesis occurs in a PLC- and PKC-dependent manner involving elevated Ca 2+ responses and c-fos expression [35, 89, 125], and it has been shown that AVP strongly regulates the GATA-4 transcription factor in hypertrophied cardiomyocytes [127]. Interestingly, V1AR regulation of GATA-4 may also aid in ventricular precursor differentiation and maturation as V1AR mediates GATA-4 during D3 embryonic stem cell differentiation via the NOS pathway [128]. Studies examining the expression of vasopressin receptors on rat hearts have shown that although V2R expression is barely detectable in adult rat hearts, its expression increases until post-natal day 5 and then declines [129].…”
Section: Cardiac Cell Type-dependent V1ar Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…V1AR-mediated protein synthesis occurs in a PLC- and PKC-dependent manner involving elevated Ca 2+ responses and c-fos expression [35, 89, 125], and it has been shown that AVP strongly regulates the GATA-4 transcription factor in hypertrophied cardiomyocytes [127]. Interestingly, V1AR regulation of GATA-4 may also aid in ventricular precursor differentiation and maturation as V1AR mediates GATA-4 during D3 embryonic stem cell differentiation via the NOS pathway [128]. Studies examining the expression of vasopressin receptors on rat hearts have shown that although V2R expression is barely detectable in adult rat hearts, its expression increases until post-natal day 5 and then declines [129].…”
Section: Cardiac Cell Type-dependent V1ar Signalingmentioning
confidence: 99%
“…Studies examining the expression of vasopressin receptors on rat hearts have shown that although V2R expression is barely detectable in adult rat hearts, its expression increases until post-natal day 5 and then declines [129]. The V2R expression and presence of AVP in maturing hearts suggests that V2R may play a role in cardiac development and maturation; indeed, while V1AR is mainly responsible for ventricular differentiation of embryonic stem cells, V2R were shown to modulate atrial precursor cell differentiation [128]. …”
Section: Cardiac Cell Type-dependent V1ar Signalingmentioning
confidence: 99%
“…We demonstrated that undifferentiated hASCs and differentiated adipocytes express the V1a receptor, but not the V1b or V2. This observation differs from mouse embryonic stem cells that express all three receptor subtypes (Gassanov et al, 2007). It is possible that the pluripotent nature of embryonic stem cells compared to multipotent adult stem cells may be accountable for this variation.…”
Section: Discussionmentioning
confidence: 58%
“…To investigate the effect of AVP on adipogenesis, we supplemented the differentiation medium with 100 nM AVP which enhances differentiation of other cell types (Gassanov et al, 2007; Gutkowska et al, 2007; Nervi et al, 1995). AVP supplementation reduced lipid droplet accumulation as determined by ORO staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation